Propuesta para la implementación de un plan de marketing digital para la empresa distribuciones multifer de villavicencio (2021)
This work aims to design and present a proposal for the implementation of digital marketing for the company Distribuciones Multifer, in this process it was done through a descriptive approach where it allowed to observe the information of the company inside and outside that allowed to start the current strategies and future strategies to implement. Through an interview with the owner of the company it was possible to deduce weaknesses and strengths that are intended to be addressed through the proposal, after this analysis was conducted it was found that it would be positive not only against a competition but also against customers and suppliers who will see this as an opportunity to expand operations, having improvements in promoting the company, communication in the process and an increase in sales through digital channels, as a final recommendation the use of social networks may be significant for an entry into the digital market, to have proximity to loyal customers and potential customers, achieving consumer confidence.